Implementasi Arsitektur MERN Stack Pada Sistem Informasi Penjualan UMKM Dapur Si Mbok Dengan Tinjauan Performa Terhadap Native Programming - Maheswara Abhista Hamdan Hafiz; Oman Komarudin; Intan Purnamasari (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Dapur Si Mbok is a home-based micro-enterprise selling traditional culinary products in Purwasari District, Karawang Regency, facing challenges such as a conventional sales system, limited promotion, and manual transaction recording. Digitalization through third-party platforms (GoFood, GrabFood) proved less effective, as high service fees reduced the competitiveness of product pricing. This study aims to design a web-based information system to support online sales for Dapur Si Mbok using the Prototype method with MERN Stack technology (MongoDB, Express.js, React.js, Node.js). The system includes authentication, product management, shopping cart, order processing, Midtrans Snap payment integration, online/offline transaction recording, sales reports, and order notifications, deployed on Railway with MongoDB Atlas as the database. Testing consisted of Black-box Testing (44 scenarios, all valid), White-box Testing (Cyclomatic Complexity of 5 for createOrder() and 7 for handlePaymentNotification()), User Acceptance Testing (a score of 94.00%, categorized as Very Good), and performance testing showing that the MERN Stack architecture achieved higher throughput and greater stability compared to native programming. The results indicate that the Prototype method is effective for developing web-based information systems for MSMEs (Micro, Small, and Medium Enterprises), and that the resulting system successfully addresses the operational issues faced by Dapur Si Mbok.